Louise Glück’s «Wild iris» in the light of cultural heritage of Judaism - Piatrovich, Aliaksandra Yu. (Journal of the Belarusian State University. Philology, 2019)
This article discusses philosophical and theological problems in the poetry collection «Wild iris» by Louise Glück, Pulitzer Prize winner (1993) and United States Poet Laureate (2003–2004). Multiple connections to the religious literature of Judaism and works by prominent 20th century Jewish theologian Abraham Joshua Heschel are made. The author refers to contemporary research of the Bible in its historical, linguistic and literary context. The historical development of some terms that are widely used in Anglo-American literary criticism is described at length. Questions of Biblical perception of the world are discussed along with the questions of modern Western Judeo-Christian worldview. Close attention is paid to the humanistic and spiritual depth of L. Glück’s poetry and its broad cultural context. The analysis of some selected poems allows us to draw conclusions about the ways in which the problems of immanence and transcendence, along with the metaphysical existence of God and human response to it, are reflected in L. Glück’s works. The topicality and novelty of the chosen subject stem from the fact that L. Glück’s poetry remains mostly unknown to Belarusian scholars despite being well-acknowledged in the American literary circles.